Antenas Fabry-Pérot con apertura uniforme y mejora del ancho de banda. - Mateos-Ruiz, Pablo; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (My University, 2024)
A design methodology to realize Fabry-Pérot cavity antennas with very high aperture efficiency and improved bandwidth is presented. The antenna is based on a tapered Partially Reflective Surface, and its characteristics are determined through a combination of criteria from the simplified ray-model and the 2D leaky-wave approaches. Therefore, through a transmission line modelling of the PRS, its cells can be chosen to follow the required leakage factor function while satisfying the resonance condition and the positive phase-slope technique. Two different designs are carried out to present a quasi-uniform aperture field distribution. Their simulated behaviours are compared with the best design of a previous work, clearly showing the improvement achieved from incorporating the leaky-wave theory into these antennas.
Keywords: Redes de antenas; Antenas Fabry-Pérot; Onda de fuga bidireccional; Apertura uniforme; Modulación espacial; Ancho de banda mejorado